Parameterization of hydrostatic behavior of deployable hypar umbrellas as flood barriers. (June 2021) - Wang, Shengzhe; Notario, Vanessa; Garlock, Maria; Glisic, Branko
Abstract: Deployable four-sided hyperbolic paraboloid (hypar) umbrellas inspired by the architecture of Félix Candela have been conceptualized as a feasible countermeasure against surge-induced coastal inundation. Referred as Kinetic Umbrellas, such structures may readily deploy from an open canopy to form a physical barrier prior to imminent coastal hazard scenarios. This paper presents a parametric investigation into the structural behavior of Kinetic Umbrellas exhibiting rise/area ( r ∕ A ) ratios from 0 to 0.045 m −1 subject to hydrostatic inundation ranging from 50% to 100% of the total deployed height. An analytical method for the discretization of hydrostatic forces on tilted hypar manifolds was developed and validated, enabling the determination of internal forces and deformations within the umbrella and supporting column via finite element modeling. All critical demands were highly influenced by the lateral column rigidity for any given r ∕ A, to which a ratio of 0.03 m −1 was revealed as optimal for the minimization of shell stresses. Longitudinally asymmetric umbrellas were also analyzed and were discovered to exhibit inferior structural performance relative to their doubly-symmetric counterparts. Finally, concrete reinforced with glass fiber polymers was demonstrated as a feasible material for such structures even at the maximum level of inundation. This work ultimately provides insight into the holistic response of Kinetic Umbrellas to aid their prototyping and design for practical engineering applications. Highlights: Analytical method developed to model hydrostatic inundation on Kinetic Umbrellas. Hypar geometry significantly reduces moment and shear forces in the umbrella. Internal forces strongly influenced by lateral stiffness of supporting column. Case study revealed a 100 mm shell can withstand over 7 m of surge inundation.